2022
DOI: 10.1021/acssuschemeng.2c06508
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Conductive Bifunctional Nanocellulose-Reinforced Robust and Self-Healable Electronic Skin: Deep Insights into Multiple Bonding Network, Property Reinforcement, and Sensing Mechanism

Abstract: The rapid development of intelligent electronic skin with skin-like protein structures and noninvasive adhesion to the skin has attracted attention in the field of wearable electronics. However, poor mechanical strength, narrow sensing range, and low adhesion hinder its practical applications. Herein, a multifunctional composite sensor (SCGC) was achieved by incorporating an intrinsically conductive bifunctional nanocellulose (CNFene) into a Ca 2+ /glycerin (GL)-modified silk fibroin (SF) matrix. The SCGC film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…(a) ( R – R 0 )/ R 0 change of PVA/CP 40 under different strains, (b) mechanism illustration of change of conductive paths in PVA/CP 40 at different states, (c) comparison of GF with this work: CNCs–polyanilin/polyvinyl alcohol (CNC–PANI/PVA), poly [2-(methacryloyloxy) ethyl] dimethyl-(3-sulfopropyl), and acrylamide ionogel fibers [P­(SBMA- co -AM) IGFs], silkworm cocoon glycerin-2% cellulose nanofiber graphene (SCGC-2% CNFene), polyacrylamide/carboxymethylcellulose (PAAm/CMC), cellulose nanofiber pyrrole iron­(III)/polyvinyl alcohol (CNF Fe /PVA), 0.8 wt % multi-branched CNCs/polyvinyl alcohol (0.8 wt % MPVA/CNC), CNCs/methyl methacrylate/polyvinyl alcohol (CNC/MMA/PVA), thermoplastic elastomer and carbon nanotubes film (TPE/CNTs film), silk-crosslinked polyelectrolyte hydrogels (SCPEHs), conductive silk fibroin hydrogel (CSFH), and thermoplastic polyurethane-0.6 wt % graphene (TPU-0.6G), (d) response time and relaxation time of PVA/CP 40 , and (e) ( R – R 0 )/ R 0 change of PVA/CP 40 with 1600 stretching–releasing cycles from 0 to 40% at 40%/s, and the insets exhibited enlarged images of 256–265, 748–757, and 1460–1469 cycles, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) ( R – R 0 )/ R 0 change of PVA/CP 40 under different strains, (b) mechanism illustration of change of conductive paths in PVA/CP 40 at different states, (c) comparison of GF with this work: CNCs–polyanilin/polyvinyl alcohol (CNC–PANI/PVA), poly [2-(methacryloyloxy) ethyl] dimethyl-(3-sulfopropyl), and acrylamide ionogel fibers [P­(SBMA- co -AM) IGFs], silkworm cocoon glycerin-2% cellulose nanofiber graphene (SCGC-2% CNFene), polyacrylamide/carboxymethylcellulose (PAAm/CMC), cellulose nanofiber pyrrole iron­(III)/polyvinyl alcohol (CNF Fe /PVA), 0.8 wt % multi-branched CNCs/polyvinyl alcohol (0.8 wt % MPVA/CNC), CNCs/methyl methacrylate/polyvinyl alcohol (CNC/MMA/PVA), thermoplastic elastomer and carbon nanotubes film (TPE/CNTs film), silk-crosslinked polyelectrolyte hydrogels (SCPEHs), conductive silk fibroin hydrogel (CSFH), and thermoplastic polyurethane-0.6 wt % graphene (TPU-0.6G), (d) response time and relaxation time of PVA/CP 40 , and (e) ( R – R 0 )/ R 0 change of PVA/CP 40 with 1600 stretching–releasing cycles from 0 to 40% at 40%/s, and the insets exhibited enlarged images of 256–265, 748–757, and 1460–1469 cycles, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the insets showed that the response time and relaxation time of the composite film under instantaneous tension were 172 and 183 ms, respectively. This demonstrated when the film was stimulated by rapidly changing external motion, the response signal could be quickly and accurately captured, which was 54 silkworm cocoon glycerin-2% cellulose nanofiber graphene (SCGC-2% CNFene), 6 polyacrylamide/carboxymethylcellulose (PAAm/CMC), 55 cellulose nanofiber pyrrole iron(III)/polyvinyl alcohol (CNF Fe /PVA), 29 0.8 wt % multi-branched CNCs/polyvinyl alcohol (0.8 wt % MPVA/CNC), 33 CNCs/methyl methacrylate/polyvinyl alcohol (CNC/MMA/PVA), 56 thermoplastic elastomer and carbon nanotubes film (TPE/CNTs film), 57 silk-crosslinked polyelectrolyte hydrogels (SCPEHs), 58 conductive silk fibroin hydrogel (CSFH), 59 and thermoplastic polyurethane-0.6 wt % graphene (TPU-0.6G), 60 crucial for practical applications. In order to further evaluate the long-term dynamic stability and durability of PVA/CP 40 , it was subjected to 1600 stretching−releasing cycles of 40% strain at a rate of 40%/s (Figure 5e).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 The addition of CaCl 2 in plasticized silk films has also been shown to decrease Young's modulus with the increasing CaCl 2 concentration and increase elongation at break. 57 Molecular simulations demonstrated that while Ca ions had a negligible effect on hydrogen bonds in the silk matrix and secondary structure, the increased water uptake in silk films due to plasticizers decreased the crystalline strength while introducing structures conducive to stretchability. 36 Incorporating methacryloxypropyl-terminated PDMS (P-PDMS) with PF not only doubles tensile strength but also increases film brittleness (note that no plasticizer is used).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Flexible wearable electronic devices have attracted a significant amount of interest in the fields of human motion detection, health monitoring, electronic skins, flexible sensors, and soft robotics because of their large mechanical flexibility and their ability to adapt to different working environments to a certain extent and meet different deformation requirements. Among a wide variety of sensing materials, hydrogels show great application potential due to their functionality, formability, and chemical editability. Although the application value of hydrogel sensors in detecting body movement and vital signs has been proven, their practical application is still significantly limited, which is mainly caused by the inherent properties of hydrogels. The first inherent property that hinders the practical application of hydrogels as flexible wearable electronic devices is swelling behavior. Hydrogel is a kind of soft material composed of a three-dimensional polymer framework with high water content. For obtaining good biocompatibility, this three-dimensional polymer framework is generally designed as hydrophilic polymer segments, which will lead to the swelling behavior of the hydrogel in the aqueous environment. Swelling behavior is usually accompanied by the introduction of a large number of solvent substances and the dilution or loss of functional molecules. Meanwhile, the decrease of hydrogel density caused by swelling behavior also has a significant negative impact on the mechanical properties of hydrogels. The second inherent property is the low-temperature phase transition behavior of hydrogels.…”
Section: Introductionmentioning
confidence: 99%